2009
DOI: 10.7589/0090-3558-45.2.519
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Influenza A and B Viruses in South American Fur Seals (Arctocephalus australis)

Abstract: ABSTRACT:The aim of this work was to detect serologic evidence of influenza virus infections in South American fur seals (Arctocephalus australis) that inhabit the Uruguayan coast. In 29 of 37 serum samples that were analyzed, we identified antibodies to at least one of the following antigens: H1N1 (A/NewCaledonia/ 20/99), B/Beijing/184/93-like viruses, B/Hong Kong/330/01, and B/Sichuan/379/99 by means of the hemagglutination inhibition assay (HAI). Results confirmed that influenza A viruses circulate in marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 16 publications
0
31
0
9
Order By: Relevance
“…Influenza A viruses (IAVs) are distributed globally and can infect a wide range of host species, including humans , birds (Chen & Holmes, 2010), pigs , horses , dogs , cats (Ali et al, 2011) and seals (Blanc et al, 2009). Wild waterfowl are considered the natural IAV reservoir (Taubenberger & Kash, 2010) and a genetically distinct lineage of viruses has also been identified in bats (Tong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A viruses (IAVs) are distributed globally and can infect a wide range of host species, including humans , birds (Chen & Holmes, 2010), pigs , horses , dogs , cats (Ali et al, 2011) and seals (Blanc et al, 2009). Wild waterfowl are considered the natural IAV reservoir (Taubenberger & Kash, 2010) and a genetically distinct lineage of viruses has also been identified in bats (Tong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By Hemagglutination Inhibition Assay (HAI) it was found that all the positive samples reacted with A/New Caledonia/20/99(H1N1) antigen reaching HAI titer of 320 but none of the sampled serum reacted with A/Panamá/2007/99(H3N2) antigen. For the first time, the presence of influenza A in A. australis was confirmed (Blanc et al, 2009) (Fig. 6).…”
Section: Evidence Of Influenza Virus Infections In Arctocephalus Austmentioning
confidence: 66%
“…Indirect evidence of influenza A viruses has been reported in 27% of the South American fur seals sampled in Uruguay (Blanc et al, 2009). By Hemagglutination Inhibition Assay (HAI) it was found that all the positive samples reacted with A/New Caledonia/20/99(H1N1) antigen reaching HAI titer of 320 but none of the sampled serum reacted with A/Panamá/2007/99(H3N2) antigen.…”
Section: Evidence Of Influenza Virus Infections In Arctocephalus Austmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, isolation of M. pinnipedii in pups without gross lesions indicates that the bacterium is acquired in early stages of their life. Serological studies have reported exposure to influenza A and B viruses in SAFS pups in Uruguay [36], but it is unknown if it could act as a primary or predisposing cause of respiratory infections. In the New Zealand sea lions, pulmonary and systemic infections by Klebsiella pneumoniae have contributed to significant pup mortality [21], but it is unknown if this bacteria could be affecting SAFS.…”
Section: Discussionmentioning
confidence: 99%